Total Phenolic and Flavonoid Content, Antioxidant, and Toxicity Test with BSLT of Meistera chinensis Fruit Fraction from Southeast Sulawesi - Musdalipah Musdalipah; Selfyana Austin Tee; Karmilah Karmilah; Sahidin Sahidin; Adryan Fristiohady; Agung Wibawa Mahatva Yodha (Borneo Journal of Pharmacy, 2021)
Zingiberaceae have a large number of species and still need research to reveal their chemical content. Meistera chinensis is one of the new generations of the Zingiberaceae family, a local and widespread plant in Konawe Regency, Southeast Sulawesi. Empirically, M. chinensis is used as a flavor enhancer in food, aches, and increases body immunity. There are no reports of chemical content or its biological activity. In this study, the fruit of M. chinensis was tested for phytochemicals, antioxidants using the ABTS test, total phenolic, total flavonoid content, and toxicity test with a lethal test for brine shrimp (BSLT). Meistera chinensis was extracted with ethanol and fractionated by ethyl acetate solvent using vacuum liquid chromatography. Phytochemical screening was carried out qualitatively by using the calorimetric method. The fraction toxicity was monitored by BSLT. These fractions for the ABTS method obtained fractions 1-8 (F1-F8) and ascorbic acid were used as controls. The results showed radical scavenging activities fraction of M. chinensis fruit was a very strong activity with IC50 of 42.7±3.53 mg/L (F8). The total phenolic and flavonoid contents were 30.72±1.07 mgGAE/g and 8.02±0.48 mgQE/g, respectively. The phytochemical evaluation contains terpenoids, saponins, phenolics, steroids, alkaloids, and flavonoids. The BSLT toxicity test was found to be very toxic, with an IC50 of 5.2±0.72 mg/L. These findings indicate that the fruit of M. chinensis acts as an antioxidant and toxicity agent.